A Colorimetric and Fluorescent Dual-Mode Sensor Based on a Smartphone-Assisted Laccase-like Nanoenzyme for the Detection of Tetracycline Antibiotics - Hongyue Chen; Zining Wang; Qi Shi; Weiguo Shi; Yuguang Lv; Shuang Liu (Nanomaterials)
A copper-based nanoenzyme (Cu-BL) co-modified by L-L-lysine and 2-2-amino terephthalic acid has laccase-like activity and fluorescence characteristics. Based on this, a colorimetric and fluorescent dual-mode sensor was developed to visually and quantitatively detect tetracycline antibiotics (TCs), including tetracycline (TC), chlortetracycline (CTC), and oxytetracycline (OTC). In the colorimetric detection system, TCs can inhibit the generation of singlet oxygen (1O2) and weaken the ability of 2,4-dichlorophenol (2,4-DP) to be oxidized into pink-colored quinone substances. The linear ranges are 0.5–80 μM, 1–80 μM, and 0.25–80 μM, and the detection limits are 0.27 μM, 0.22 μM, and 0.26μM, respectively. In addition, due to the inner filter effect, tetracycline antibiotics can interact with Cu-BL, and with the increase in tetracycline antibiotic concentration, the fluorescence intensity will decrease. In addition, the smartphone sensing platform is combined with the colorimetric signal for the rapid and visual quantitative detection of tetracycline antibiotics. Generally speaking, the colorimetric/fluorescence dual-mode sensor demonstrates good stability, high specificity, and strong anti-interference capabilities, highlighting its practical application potential. This work is expected to offer novel insights for the development of multifunctional nanoenzymes and the integration of a multi-mode sensing platform.